2015
DOI: 10.2337/db15-0054
|View full text |Cite
|
Sign up to set email alerts
|

c-Kit Receptor Signaling Regulates Islet Vasculature, β-Cell Survival, and Function In Vivo

Abstract: The receptor tyrosine kinase c-Kit plays an integral role in maintaining b-cell mass and function. Although c-Kit receptor signaling promotes angiogenesis in multiple cell types, its role in islet vasculature is unknown. This study examines the effects of c-Kit-mediated vascular endothelial growth factor isoform A (VEGF-A) and islet vascularization on b-cell function and survival using in vitro cell culture and in vivo mouse models. In Increasing evidence suggests that c-Kit and its ligand, stem cell factor (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…c-kit + cells have been shown to be self-renewing, clonogenic, and multipotent both in vitro and in vivo in hearts, lungs, and other organs [2224]. Furthermore, c-kit and its ligand, stem cell factor, are both expressed in the CNS and the peripheral nervous system [2528], as well as in the retinas of humans and mice [2932].…”
Section: Introductionmentioning
confidence: 99%
“…c-kit + cells have been shown to be self-renewing, clonogenic, and multipotent both in vitro and in vivo in hearts, lungs, and other organs [2224]. Furthermore, c-kit and its ligand, stem cell factor, are both expressed in the CNS and the peripheral nervous system [2528], as well as in the retinas of humans and mice [2932].…”
Section: Introductionmentioning
confidence: 99%
“…We further evaluated whether up-regulation of Igf-2 and Akt signaling could enhance islet Vegf-a levels, a major factor associated with increased islet growth [22], and islet vascularization in the developing fetal pancreas. We found that MIP-βIRKO islets had elevated pancreatic Vegf-a protein levels as determined by immunofluorescence (Figure 5A) and western blotting ( p < 0.01 vs .…”
Section: Resultsmentioning
confidence: 99%
“…The loss of insulin receptor (IR) expression on pancreatic β-cells during 2 nd transition of the pancreatic development results in enhanced secretion of insulin growth factor-2 (Igf-2). B. Autocrine/paracrine activation of the insulin growth factor-1 receptor (Igf-1r) on pancreatic β-cell by Igf-2 promotes Akt phosphorylation, leading to: (1) suppressed phospho-p53 (S15) activation that prevents β-cell apoptosis, and (2) increased secretion of vascular endothelial growth factor-a (Vegf-a) through the Akt/HIF-1/Vegf-a signaling pathway in β-cells [22]. C. Together, Vegf-a-mediated hyper islet vascularization and upregulated Akt activity promotes exaggerated β-cell replication and cell survival, leading to an expanded β-cell population within the pancreas of MIP-βIRKO animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations